Elective nodal irradiation or involved-field irradiation in definitive chemoradiotherapy for esophageal squamous cell cancer: a retrospective analysis in clinical N0 patients - Sun, Y. (Curr Oncol, 2018)
OBJECTIVE: We compared failure patterns and survival after elective nodal irradiation (eni) or involved-field irradiation (ifi) in patients with thoracic esophageal squamous cell carcinoma (escc), clinical stage T2–4N0M0, to determine whether ifi is feasible for such patients. METHODS: Between 2005 and 2015, 126 patients with clinical stage T2–4N0M0 thoracic escc who received definitive concurrent chemoradiotherapy in Shandong Cancer Hospital and Institute and who had complete data, were analyzed retrospectively. Of those patients, 49 received ifi, and 77 received eni. In the ifi group, the radiation field included the primary tumour, with a 3-cm to 4-cm margin in the craniocaudal direction, and the elective irradiation was delivered to the adjacent regional lymphatics according to the location of the primary tumour. Patterns of failure were classified using the first site of failure, which included primary tumour failure, regional lymph node failure, and distant metastasis. RESULTS: Median progression-free survival was 20 months [95% confidence interval (ci): 7.87 months to 39.2 months] in the ifi group and 30 months (95% ci: 17.4 months to 44.6 months) in the eni group (p = 0.580). Median overall survival (os) was 36 months (95% ci: 21.9 months to 50.1 months) in the ifi group and 38 months (95% ci: 26.1 months to 49.9 months) in the eni group (p = 0.761). The estimated 1-year, 3-year, and 5-year os rates were, respectively, 87.8%, 49.4%, and 32.3% for the ifi patients and 92.2%, 52.0%, and 28.9% for the eni patients. Disease persistence and primary lesion recurrence after complete remission (cr) were the most frequent causes of treatment failure in the patients overall (83 of 124, 66.9%). Of the 66 patients achieving a clinical cr, 25 experienced recurrence of the primary lesion, 12 experienced distant relapse, 10 experienced regional nodal failure, and 2 experienced an isolated recurrence. No significant differences in the pattern of failure or in the incidences of grade 3 or greater treatment-related myelosuppression or esophagitis were found between the ifi and eni groups. CONCLUSIONS: In patients with thoracic escc clinical stage T2–4N0M0 receiving definitive chemoradiotherapy, failure patterns and os were similar with either eni or ifi. Large prospective randomized studies are needed to further investigate and verify those results in this subgroup of patients.